Effects and side effects of mydriatic eyedrops in neonates - (:unkn) unknown (Wichtig Publishing Srl, 1996)
The pupils of neonates and premature infants often need to be dilated for retinal examination. The drops used for this purpose have some known side effects. This study investigated the effects and side effects of these drops. In this prospective randomized study, 80 healthy neonates were randomly assigned to eight groups. In Group A 1% cyclopentolate was used; in Group B 1% tropicamide; in Group C 2.5% phenylephrine; in Group D 1% cyclopentolate and 1% tropicamide; in Group E 2.5% phenylephrine and 1% tropicamide; in Group F 0.5% cyclopentolate, 0.5% tropicamide and 2.5% phenylephrine; in Group G 1% cyclopentolate and 2.5% phenylephrine and in Group H 0.9% NaCl. Heart rate, systolic and diastolic blood pressures were recorded before, and 5, 10, 15, 30, 45, 60 minutes after instillation of the drops. Pupillary size was measured at baseline, 30 and 60 minutes. To stimulate the conditions of indirect ophthalmoscopic examination, the pupil sizes were measured under the intense beam of a halogen light. The results were analyzed statistically. Maximum side effects were seen in group C; the safest was group B and maximum mydriasis was achieved in group F.
Keywords: Mydriatic eye-drops; Neonates